Search for decays of the 125 GeV Higgs boson into a Z boson and a ρ or ϕ meson - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich; Sukhikh L. G. Leonid Grigorievich (2020, 2020)
Title screen